Comparison of the efficacy of Aeromonas veronii ΔhisJ vaccine in Carassius auratus via different immunization routes - Wu, Tonglei; Ma, Ruitao; Pan, Xiaoyi; Wang, Fengjie; Zhang, Zhiqiang; Shi, Qiumei; Shan, Xiaofeng; Gao, Guisheng (Frontiers in Veterinary Science, 2024)
Aeromonas veronii is a significant pathogen to various aquatic life. Infections in fish can lead to high mortality rates, causing substantial economic losses in aquaculture. Vaccination is proposed as a substitute for antibiotics in aquaculture to decrease disease-related mortality and morbidity. Our study previously constructed a hisJ-deleted strain of A.veronii, which provided protective effect to Loache To further assess the vaccine's applicability, this study evaluated its genetic stability and safety, aAnd the immune protective effects in Carassius auratus were explored through four distinct administration routes: intraperitoneal injection, intramuscular injection, oral administration, and immersion, to determine the efficacy of these administration routes.The results showed that the vaccine strain remained genetically stable after 45 generations. Immunization via these administration routes was safe for Carassius auratus, with intraperitoneal and intramuscular injections causing stronger adverse reactions. Immersion immunization resulted in mild adverse reactions, and no significant adverse reactions were observed following oral immunization. Immunizing Carassius auratus at safe concentrations via these routes enhanced the phagocytic activity in serum, increased the levels of non-specific immune-related enzymes (ACP, AKP, C3, C4, LZM, SOD, and IgM), and improved specific serum antibody levels. It also elevated levels of cytokines related to inflammatory responses (IL-1β, IL-10, TNFα, TGF-β) in organ tissues (liver, spleen, kidney, mid-post intestine, and gills). The survival rates of Carassius auratus were measured after challenging with the virulent strain A.veronii TH0426, resulting in the relative survival rates of 64% for Intraperitoneal vaccineIpV group, 56% for Intramuscular vaccineImV group, 52% for oral vaccineOV group, and 48% for immersion vaccineIV group. This indicates that different immunization routes stimulated a certain level of immune protection in Carassius auratus. Analysis of bacterial load in the liver, spleen, and kidneys postchallenge showed a decreasing trend in the control group, indicating that the vaccine strain ΔhisJ could gradually restrict the rapid proliferation of bacteria in these tissues, thereby providing a certain level of immune protection against A. veronii. In brief, the vaccine strain ΔhisJ can serve as a safe live attenuated vaccine for Carassius auratus, and this study lays the foundation for the development of live attenuated vaccines against Aeromonas veronii.